"Husbands Are Pregnant, Too": Caring Masculinities in Pregnancy Books for Men. Issue 2 (June 2023) - Allan, Jonathan A.
This article studies pregnancy books that are written largely by men for men and that account for men's roles in pregnancy. Drawing on an analysis of the texts themselves, this study shows recurring themes across these books, which include: Expecting, too! which frames men as having a role in pregnancy beyond fertilization; fatherhood as a rite of passage; Unlike our dads, in which men are taught to be different from their fathers recognizing that expectations of fathers have changed; and, expectations of expectant fathers, namely, how men are to be caring partners. This article explores how these books frame masculinity and the roles men play in pregnancy. This article thus shows how these books contribute to a growing body of scholarship interested in "caring masculinities."